PROFIL MINAT BACA MAHASISWA FKIP UNIVERSITAS BENGKULU - Gum Gumono (Universitas Bengkulu, 2016)
This research aimed at mapping the reading interest of the faculty of teacher training and education students. This profiling was considered important as the result can be used as the basis for the curriculum developers in improving students’ reading skill. This research was conducted by using descriptive quantitative method. The location was at the Faculty of Teacher Training and Education University of Bengkulu involving random sample. The data was collected by using a test and a survey. The result shows that: first, the reading interest of the students is categorized as low. Second, the students seldom make use of their time either for reading or visiting the library. Third, the most preferred books to read are popular books (politics, training, education, and motivation books), while scientific textbooks are less favored. Fourth, students only use less than one hour a day for reading.